PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW BERBANTUAN MEDIA POSTER TERHADAP HASIL BELAJAR SISWA KELAS X SEKOLAH MENENGAH ATAS - Rohi, Yachob; Bano, Vidriana Oktoviana; Ndjoeroemana , Yohana (Dharmas Education Journal (DE_Journal), 2023)
This research intends to identify the effect of the jigsaw-type cooperative educational form on the learning outcomes of students in the X MIPA category at SMA Negeri 1 Rindi Umalulu. This type of research is based on the concept of using a pretest-posttest with a control design team. Collection of illustrations using purposive sampling. The population in this research is made up of students in the X MIPA category in the even semester of the year 2022 or 2023. An illustration of this research is that there are 36 teaching participants in the X MIPA 2 category as the supervisory category and 36 X MIPA 1 teaching participants as the research category. The results of the analysis obtained from the posttest scores prove that the scores in general for the larger research category are 74.22, greater than those for the surveillance category, which are 66.69. Not only that, from the experimental results assuming the paired sample t-test, the sig (2-tailed) is 0.000  0.05, so it can be concluded that the form of cooperative upgrading of the jigsaw type assisted by a placard affects the learning outcomes of students.